Stakeholder awareness of climate adaptation in the commercial seaport sector: A case study from Ireland. (January 2020) - O'Keeffe, Jane M; Cummins, Valerie; Devoy, Robert J N; Lyons, Donald; Gault, Jeremy
Abstract: Seaports as critical shore-based infrastructure are particularly vulnerable to impacts such as sea level rise and increasing incidents of severe weather events. In excess of ninety percent of global trade by volume is transported by sea. In Ireland, seaports are of strategic importance to the national economy. As an island nation, ninety eight percent of trade by volume comes through its seaports. Climate issues facing Irish ports include increasing storminess, such as the Atlantic storms experienced in the winter of 2014. Ireland provides a particularly valuable case study as the scale of Irish port sizes, analysed in this research, range from 500, 000 to 30 million throughput tonnage. This tonnage range, is more typical of port sizes globally, and adds relevance to the study. The specific objectives of this paper are to establish the readiness of the seaport sector in Ireland to build adaptive capacity to respond to climate change and to assess lessons from and for Ireland in the context of international best practice. The research identified a lack of awareness and understanding of climate change amongst the sample population of seventy senior managers (comprising of national regulators and local authorities; commercial port harbour companies; and indigenous and multinational industries located in the port hinterland), as representatives of the maritime sector in Ireland. Evidence of a knowledge gap was identified from in-depth semi-structured interviews conducted over a twelve month period. Many industry stakeholders were actually implementing adaptation measures within their organisational strategies, unaware of the explicit links with climate adaptation. Highlights: Lack of awareness and understanding of climate adaptation in the maritime sector. Evidence of a knowledge gap identified amongst industrialists and regulators surveyed. Port environmental management systems form pathways to adaptive capacity building. Adaptive capacity is dependent on the accuracy of vulnerability and risk assessment. Stakeholder collaboration has the potential to deliver successful adaptation.